The effect of audit materiality disclosures on investors’ decision making - Christensen, Brant E.; Eilifsen, Aasmund; Glover, Steven M.; Messier, William F. (Accounting, Organizations and Society, 2020)
Recent reviews of the academic literature indicate that little is known regarding how users evaluate the materiality levels auditors use or respond to quantitative materiality disclosure. Regulators around the world have taken different stances on whether materiality should, or should not, be disclosed in the auditor’s report. In response to the dearth of research on these policy decisions, we examine the effect of audit materiality disclosures, or lack thereof, on professional investors’ decision making across different investment contexts (debt vs. equity, public vs. private). Our study is designed to test global audit public policy and as such our hypotheses are motivated by assertions made by regulators, auditing standards, and audit theory. Among a sample of 246 professional investors in our main experiment and 91 professional investors in two supplemental experiments, we find no consistent evidence that investors incorporate materiality disclosures into their investment decisions. Most importantly, we find evidence that investors’ understanding of materiality is not in line with regulator assertions. For example, investors fail to make consistent connections between the amount of disclosed audit materiality and the level of auditor effort. Our results hold across debt and equity investment settings for both public and private companies. In sum, our findings suggest that disclosures of audit materiality are not well understood by professional investors and are not viewed as decision relevant. This research informs practitioners, regulators, and academics regarding the effect of materiality disclosure on investor decision making as well as stakeholders’ views and expectations of overall materiality.